Alterations in binding characteristics of the human immunodeficiency virus enhancer factor. - Wu, F (1988)
Five regions of the human immunodeficiency virus (HIV) long terminal repeat (LTR) serve as binding sites for cellular proteins as demonstrated by DNase I footprinting. These include the negative regulatory, enhancer, SP1, TATA, and untranslated regions. The HIV enhancer region contains two direct repeats of a sequence, GGGACTTTCC, which is also found in the enhancer sequences of simian virus 40, cytomegalovirus, and the immunoglobulin kappa gene. To further characterize binding to the enhancer sequences in the HIV LTR, DNase I footprinting was performed using extracts prepared from several different cell lines. Extracts prepared from lymphoid cells gave altered binding over the enhancer region as compared with extracts prepared from either monocytes or HeLa cells. This altered binding in extracts prepared from lymphoid cells resulted in protection of both direct repeats in the HIV LTR in contrast to complete protection of only one direct repeat with HeLa cell extracts. When HeLa cells were treated with phorbol esters in either the presence or absence of the protein synthesis inhibitor cycloheximide, the binding characteristics over the enhancer element became similar to those seen in extracts prepared from lymphoid cells. These results suggest that phorbol esters may induce posttranslational modifications of cellular transcription factors that alter their DNA-binding characteristics.